صناعة المثال في تعرف المصطلح النحوي ضمن المعجم المدرسي - بلاهدة، فريدة (المجلس الأعلى للغة العربية, 2023)
يتناول هذا المقال مفهوم المثال النحوي وأهميته في تقديم النماذج الموضحة للقاعدة النحوية داخل المعجم المدرسي؛ حيث ركزنا على أهم وظيفة للمثال النحوي وهي الوظيفة التركيبية التي مهمتها توضيح مكانة المفردة داخل تركيب معين ليحسن مستخدم المعجم استعمالها في تراكيب صحيحة. ومن ثم بينا كيف يمكن للمعجم بطريقة التعريف الذي يقدمه إضافة إلى الأمثلة أن يعطي للتلميذ الأداة الأساسية التي من خلالها يستطيع بناء لغته. بعدها قمنا بدراسة تطبيقية ركزنا فيها على كيفية تناول كل من معجم أكسفورد وروبير كوليج والمنجد الوسيط للمثال النحوي بعدما قمنا بعملية إحصائية في كل منها عن مدى استعمال المثال النحوي مع المصطلحات النحوية وعن نوع المثال المستخدم في ذلك. This article discusses the concept of grammatical example and its importance in the presentation of clarified models of the grammatical rule in the school dictionary. Where we have focused on the most important function of the grammatical example which is the structural function whose task is to clarify the position of the word in a structure so that the user of the dictionary can improve its use in correct sentences. And then we showed how the dictionary by the definition it gives, in addition to the examples, can give the student the basic tool through which he can construct his language. Then we conducted an applied study in which we focused on how Oxford Dictionary, Robert College and Al-Munjid Al Wassit handled the grammatical example after performing a statistical process in each of them on the extent to which the grammatical example is used with grammatical terms and the type of example used.
Keywords: اللغة العربية -- المعاجم العربية -- المصطلحات النحوية -- الاحتجاج اللغوي